Interaction of Radiation and Turbulent Natural Convection: A Pseudo-Direct Numerical Study (Advances in Applied Mathematics and Mechanics, 2022)
This paper presents a hybrid lattice Boltzmann solver for turbulentbuoyancy-driven flow coupled with surface thermal radiation. The two-relaxationtime scheme for the Boltzmann equation combined with the implicit finite differencescheme for the energy equation is implemented to compute the heat transfer and fluidflow characteristics. The accuracy and robustness of the hybrid approach proposed inthis study are assessed in terms of the numerical and experimental data of other researchers. Upon performing the simulation, the Rayleigh number is ranged from 108to 1010 whereas the surface emissivity is changed from zero to unity. During computations, it is found that the overall temperature of the cavity is increased as a result ofenhancing the surface radiation. Convective plumes are formed both at the isothermaland the thermally-insulated walls with the $Ra≥10^9$ and $ε≥0.6.$ In the conditions understudy, the overall heat transfer rate is raised by around 5% when taking into accountthe surface thermal radiation.